2017
DOI: 10.1158/1078-0432.ccr-16-2267
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Trial of Dovitinib in BCG-Unresponsive Urothelial Carcinoma with FGFR3 Mutations or Overexpression: Hoosier Cancer Research Network Trial HCRN 12-157

Abstract: Purpose To assess the clinical and pharmacodynamic activity of dovitinib in a treatment resistant, molecularly enriched NMIUC population. Experimental Design A multi-site pilot phase 2 trial was conducted. Key eligibility criteria included: BCG unresponsive NMIUC (≥ 2 prior intravesical regimens) with increased phosphorylated FGFR3 (pFGFR3) expression by centrally analyzed immunohistochemistry (IHC+) or FGFR3 mutations (Mut+) assessed in a CLIA-licensed laboratory. Patients received oral dovitinib 500 mg dai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…HistoGel plugs were paraffin embedded and slides were prepared by the laboratory of Dr. Keith Condon (Indiana University School of Medicine; Indianapolis, IN). Samples were stained with the specified antibodies by the Indiana University School of Medicine Research Immunohistochemistry Facility (Indianapolis, IN) and quantified using the HALO image analysis platform (Indica Labs) as before 45 .…”
Section: Methodsmentioning
confidence: 99%
“…HistoGel plugs were paraffin embedded and slides were prepared by the laboratory of Dr. Keith Condon (Indiana University School of Medicine; Indianapolis, IN). Samples were stained with the specified antibodies by the Indiana University School of Medicine Research Immunohistochemistry Facility (Indianapolis, IN) and quantified using the HALO image analysis platform (Indica Labs) as before 45 .…”
Section: Methodsmentioning
confidence: 99%
“…Current clinical trials are based on proof‐of‐principle studies in cell lines and xenograft models . Phase II clinical trials of dovitinib, a multi‐targeted RTK inhibitor that prevents phosphorylation of FGFR3, showed limited activity in advanced bladder cancer and in BCG‐unresponsive bladder cancer with mutations or overexpression of FGFR3 . In contrast, a phase I trial of BGJ398 showed anti‐tumour activity in FGFR3 ‐mutated advanced bladder cancer after failure of platinum‐based chemotherapy .…”
Section: Introductionmentioning
confidence: 99%
“…Besides Pazopanib, several other substances targeting FGFRs are currently under investigation 35 and AZ12908010, AZD4547, PD173074, TKI-258/Dovitinib, SU5402 and BGJ-398 showed promising results in vitro 36 39 . Yet, clinical data is scarce and partially controversial: By systemic administration of Dovitinib biologically active concentrations could be consistently achieved in 13 patients with NMIBC 40 . However, long-term administration was not possible due to frequent toxicities.…”
Section: Discussionmentioning
confidence: 99%